Tradisi dan Masyarakat: Peran Ritus Haul Cuci Pusaka di Kota Tangerang Selatan: THE ROLE OF THE HEIRLOOM WASHING HAUL RITES IN SOUTH TANGERANG CITY - Fariz Al Hazmi (LIPI Press, 2023)
Traditions carried out and maintained by the community have a functional and symbolic role. Like the Haul Washing Heritage ritual tradition in South Tangerang City which already exists and is carried out by the Tubagus Muhammad Atif Family of Descendants. Because the implementation is so important that the tradition is preserved. The purpose of this study was to look at the phenomenon of the Haul Washing Pusaka Keramat Tajug tradition from the side of its role towards the environment in a functional and symbolic interactionist way. The research method uses qualitative methods with ethnographic types to describe the relationship between tradition and society. data collection is done by observation, semi-structured interviews, and documentation. The results show that functionally, the Haul Cuci Pusaka Keramat Tajug tradition plays a role in social interaction between the families of Tubagus Muhammad Atif's descendants and the wider community, has an impact on the surrounding economy and as a maintenance of heirlooms as the aim of carrying out the washing of heirlooms. Then, in a symbolic interactionist way, this tradition has a role as a belief to respect ancestors, as a symbol of history and the hopes of the family that owns the tradition, and as an identity for the family and cultural values ​​of the City of South Tangerang.